Perancangan Dan Analisa Kinerja Sistem Pendeteksi Frekuensi Berbasis Mikrokontroler Untuk Rentang Frekuensi 50 MHz - Rahmadnur, Khairul; Yasri, Indra (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
We propose the prototype of microcontroller-based frequency detection system by using the Arduino to capture the frequencies around it or frequencies feeding from the signal source. The reading counter is carried out by IC 74hc393. This prototype is capable to capture up to a frequency of 50 MHz then result will be displayed to the LCD display. Meanwhile, when testing the prototype validation using the direct measurements method by comparing the frequency readings using a multifunction counter and the result shows the average frequency reading of the prototype is likely accurate by 0.27 kHz.Keyword : frequency, microcontroler, frequency counter, direct measurements.